Major aspects of studying gender identity of children in the teaching and educational process - Kostyk, Liubov; Kostyk, Vasyl; Platash, Larysa; Palahnyuk, Olha (Grail of science, 2021)
The world is constantly changing and the roles of men and women in modern society are changing accordingly. In recent years, public interest in gender issues has significantly increased. Among the remarkable achievements of the indigenous science is the study of the phenomenon of gender identification, the influence of gender stereotypes and gender polarization in preschool age. In a "gendered" society, the appropriate gender-role identification of children is carried out, which determines the specifics of primary gender socialization, becomes an internal regulator of social activity of an individual. Gender, established at birth, cannot mechanically determine the type of gender identification, that is why its formation is a complex process of choosing and mastering one of the two patterns of gender behavior. The topic of our study is relevant because of the importance of the period of gender and age identification of the adolescent, whose clear and irreversible idea of his gender is being formed, as well as understanding and acceptance of the roles of sexes, recognition of the irreversibility of gender as a major component of self-awareness and self-identification. Child's gender perceptions are actively formed in preschool age and are an integral component of person's gender identity. Child masters the social norms, patterns of behavior and cultural values of his/her nation. The gender approach to the upbringing of the preschool children should be focused on the formation and establishment of equal, gender-independent opportunities for selfrealization of the individual. However as practical experience shows, the gender component and its methodological data are insufficient in terms of the content of preschool education. In preschool institutions, gender education takes place spontaneously, educators use the traditional approach to forming child's self-esteem and his stereotypes of self-perception only on the basis of gender, so it is important today to pay more attention to gender education and socialization. Experimentally it has been investigated the peculiarities of gender and age identification of the preschoolers of the preschool institution of a combined type #9 of the city of Chernivtsi. According to the research, the greater part of children of 5-6 years old are aware of their belonging to the male or female sex, having the already formed gender identity. Gender perceptions of preschool children are gender-appropriate: girls’ - feminine, and boys’ – masculine. In addition, they are stereotypical: boys have instrumental role, girls-expressive. We believe that gender approach is the theoretical ba
Keywords: : femininity, masculinity, androgyny, gender representations, gender identification, gender stereotypes, gender.